Сonducting and dielectric properties of mono- and polycrystals Na 3 Cr 2 (PO 4 ) 3 - Салиходжа , Ж. М.; Ногай, А.; Стефанович , С.; Ногай , А. С. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
This article studies the structure, conductivity and dielectric properties of polycrystalline Na 3 Cr 2 (PO 4 ) 3 . Distinctive features of the temperature of phase transitions between mono- and polycrystalline Na 3 Cr 2 (PO 4 ) 3 , although the conductive and dielectric properties of the models are practically slightly different from each other. A relationship has been established between structural changes, conductive and dielectric properties of the Na 3 Cr 2 (PO 4 ) 3 polycrystal. Models are given to explain the dielectric character of the low-temperature α –phase of Na 3 Cr 2 (PO 4 ) 3 and the superionic properties of the high-temperature γ –phase.